Understanding adaptability : a prerequisite for effective performance within complex environments - Burke, C. Shawn; Pierce, Linda G.; Salas, Eduardo (Elsevier JAI, 2006)
Adaptability is becoming a hallmark of effective performance at all levels and types of organizations. As complexity rises within the internal and external environments that organizations operate within, it is no longer acceptable to be able to perform well when things go as expected; instead individuals, teams, and organizations must be able to continuously adapt their knowledge and skills in order to remain competitive in environments which are fluid, often ambiguous, and where multiple pathways to goal attainment exist. Thus, this volume takes a multi-disciplinary approach to increasing ou.
Keywords: Organizational effectiveness.; Adaptability (Psychology); Teams in the workplace.; Organizational change.; Efficacité organisationnelle.; Adaptation (Psychologie); Équipes de travail.; Changement organisationnel.; BUSINESS & ECONOMICS -- Workplace Culture.; BUSINESS & ECONOMICS -- Corporate Governance.; BUSINESS & ECONOMICS -- Leadership.; BUSINESS & ECONOMICS -- Organizational Development.; Organizational change; Organizational effectiveness; Teams in the workplace